Analysis Of The Influence Of Financial Literature, Lifestyle, Emotional Intelligence, And Financial Technology Development On The Financial Behavior Of Yogyakarta’s Millenials Generation During The Covid-19 Pandemic - Galih Wisnu Pratama; Sri Dwi Ari Ambarwati; Agus Soekarno (Universitas Tidar, 2023)
This study is to examine the relationship between financial behavior of millennial generation during the COVID-19 pandemic which was influenced by factors such as financial literacy, lifestyle, emotional intelligence and the development of financial technology. The existence of the COVID-19 pandemic for the millennial generation certainly affects their financial behavior. The ability that has not been maximized in self-control, namely not being able to be wise in using money, not being able to control oneself when hanging out with other people and not being able to wisely face the changing times, indicates that the millennial generation still has low emotional intelligence. The results of this study were carried out descriptively or through descriptions that described and explained the research subject. Then for the approach in this research follow the steps of quantitative research work. The sample used in this study was 100 Millennials in Yogyakarta. The research variable data was processed using the Software Statistical Product and Service Solution (SPSS) version 22. The analytical methods used included descriptive statistical analysis, multiple linear regression analysis, and hypothesis testing. Financial literacy, lifestyle, emotional intelligence, and the development of fintech have a significant positive effect on the financial behavior. Financial literacy has a significant positive effect on the financial behavior. Lifestyle has a significant positive effect on the financial behavior. Emotional intelligence has a significant positive effect on the financial behavior. The development of financial technology has a significant positive effect on the financial behavior.